2011
DOI: 10.3324/haematol.2011.041814
|View full text |Cite
|
Sign up to set email alerts
|

The immunological phenotype of rituximab-sensitive chronic graft-versus-host disease: a phase II study

Abstract: 1380haematologica | 2011; 96(9) IntroductionGraft-versus-host-disease (GVHD) is the most common and life-threatening complication after allogeneic stem cell transplantation (allo-SCT).1,2 B-cell depletion with rituximab (RTX) has been successful in steroid-refractory chronic GVHD, showing response rates of 43-80%. [3][4][5][6][7][8] However, the nature of B-cell contribution, as well as to what extent B-cell depletion can restore physiological conditions, has so far not been clarified. Hypotheses obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
2
15
1
Order By: Relevance
“…22,23 In brief, target cells were labeled overnight with 100Cu 51 Cr (150Cu for primary cells) and incubated for 5 hours with transduced T cells in 5 effector-to-target ratios (E:T) between 30:1 and 0.3:1. The fold change compared with reactivity of engineered T cells expressing unmutated ␥9␦2TCR was calculated.…”
Section: Functional T-cell Assaysmentioning
confidence: 99%
“…22,23 In brief, target cells were labeled overnight with 100Cu 51 Cr (150Cu for primary cells) and incubated for 5 hours with transduced T cells in 5 effector-to-target ratios (E:T) between 30:1 and 0.3:1. The fold change compared with reactivity of engineered T cells expressing unmutated ␥9␦2TCR was calculated.…”
Section: Functional T-cell Assaysmentioning
confidence: 99%
“…If not treated therapeutically, patients were considered to be at high risk for fungal infection and received prophylaxis with voriconazole as the first choice (trough level >1 mg/dL) [23,24]. Concomitant treatments of the adult patients have been described in more detail elsewhere [25,26].…”
Section: Donor Selection and Stem Cell Processingmentioning
confidence: 99%
“…132 Correspondingly, several small trials showed clinical effectiveness of rituximab in cGVHD. GVHD of the skin responded better than cGVHD of the visceral organs, 133 but successful treatment of cGVHD of inner organs has been reported anecdotally. 134 As CD20 is a promising target not only in malignant disease several alternative, humanized or human antibodies such as ocrelizumab, GA101 and ofatumumab are currently being tested and should also be investigated in GVHD.…”
Section: B-cell Targetingmentioning
confidence: 99%